Markers of Regenerative Processes in Patients with Bipolar Disorder: A Case-control Study - Artur Reginia; Jerzy Samochowiec; Marcin Jabłoński; Ewa Ferensztajn-Rochowiak; Janusz K. Rybakowski; Arkadiusz Telesiński; Maciej Tarnowski; Błażej Misiak; Mariusz Z. Ratajczak; Jolanta Kucharska-Mazur (Brain Sciences, 2020)
Progress in medical science has allowed the discovery of many factors affecting the pathogenesis of bipolar disorder, and among the most recent research directions are found regenerative and inflammatory processes. The role of regenerative processes remains particularly poorly explored, but available data encourage further research, which may explain the pathogenesis of bipolar disorder (BD). The aim of this study was to evaluate the mobilization of stem cells into peripheral blood, in patients with bipolar disorder during stable phase, not treated with lithium salts. The study included 30 unrelated individuals with the diagnosis of bipolar disorder, with disease duration of at least 10 years, not treated with lithium salts for at least five years prior to the study. The control group consisted of 30 healthy subjects, matched for age, sex, body mass index (BMI), origin, socio-demographic factors and nicotine use. Blood samples underwent cytometric analyses to assess concentrations of: Very Small Embryonic Like (VSEL) CD34+, VSEL AC133+, HSC CD34+, HSC AC133+. There were no significant differences in stem cell levels between patients with BD and healthy controls. However, the level of VSEL cells AC133 + was significantly higher in type I BD patients compared to healthy controls. Our results indicate a disturbance in regenerative processes in patients with bipolar disorder.